2009
DOI: 10.1111/j.1758-5740.2009.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Rotator Cuff Repair Failure by Histological Analysis

Abstract: Background We aimed to determine if recognised histological features seen in specimens taken during rotator cuff repair could predict which tendon repairs were at risk of re‐rupture. Methods Forty rotator cuff tendon edge specimens from 40 patients were analysed histologically following routine mini‐open rotator cuff repair. Thirty‐two patients returned at a mean follow up of 35 months for an ultrasound examination to determine repair integrity. Results Overall there were 8 small tears, 13 medium tears, 15 lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…As expected, these findings indicate an improved tendon tissue 'quality' in Grade III patients and an increased responsiveness to biological inducers of healing response. At the same time, we should expect low reactivity in tendinopathies Grade IV, which is reflected by VVA and concordant with previous results [8]. In tendinopathies Grade III for both Group A and Group B, markers CD34, Tenascin-C, PCNA and D2-40 (p < 0.05) were significantly differentially expressed.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As expected, these findings indicate an improved tendon tissue 'quality' in Grade III patients and an increased responsiveness to biological inducers of healing response. At the same time, we should expect low reactivity in tendinopathies Grade IV, which is reflected by VVA and concordant with previous results [8]. In tendinopathies Grade III for both Group A and Group B, markers CD34, Tenascin-C, PCNA and D2-40 (p < 0.05) were significantly differentially expressed.…”
Section: Discussionsupporting
confidence: 90%
“…The anatomical and physiological features of human shoulder rotator cuff are unique [35][36][37] and have been shown to comprise critical determinants of the successful healing of partial-and fullthickness tears after surgical intervention. Matthews et al reviewed a series of cases of re-tears at a histological level and many of the tears demonstrated profound distortion of the tendon tissue [8]. Therefore, augmentation of the 'quality' of tendinopathic tissue is imperative for the later success of re-operative surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas many histological studies have addressed rotator cuff degeneration and tears, 8,9,[14][15][16][17] few studies have included specimens from a macroscopically intact portions. 13,18,19) Furthermore, it is worth mentioning that all of these studies demonstrated degeneration in macroscopically intact tendon.…”
Section: Discussionmentioning
confidence: 99%